PALINOLOGIA DA FORMACÃO SANTANA (CRETÁCEO DO NORDESTE DO BRASIL). II. DESÇRICÃO SISTEMÁTICA DOS ESPOROS DA SUBTURMA ZONOTRILETES E TURMA MONOLOTES, E DOS POLENS DAS TURMAS SACCITES E ALETES (Ameghiniana, 2013)
The present text is the second in a series of four, dedicated to the palynologic study of the Santana Formation. This part deals specifically with the systematic descriptions of 33 spores included in the Subturma Zonotriletes and Turma Monoletes, as well as 34 pollen grains belonging to the Turmae Saccites and Aletes (Subturmae Azonaletes and Appendiciferentes). Three of the described species are new: Matonisporites silvai, Crybelosporites truncatus e Paludites mamelonatus.